THE APPLICATION OF ISLAMIC VALUE AND REGIONALISM IN THE REDESIGN OF ZAINUL HASAN GENGGONG BOARDING SCHOOL IN PROBOLINGGO INDONESIA - Rozan, Nur; Setiyowati, Ernaning; Wismantara, Pudji Pratitis (Journal of Islamic Architecture, 2013)
AbstractZainul Hasan Genggong boarding school is an islamic and public school. The school has been existed from many years ago in a lack design. The amount of the room also need to be added. That is why the redesign of this building should be done. The redesign of the school have an objective to improve and develop the education quality. The design theme used in the new design is reinvigorating tradition from Pendhalungan culture. There are some islamic values in Pendhalungan culture and tradition, i.e. Ma’iyyah (togetherness) concept, modest concept, and not  excessive concept. The three islamic concept together with the Pendhalungan culture atmosphere are showed into the whole aspect of the new design, including site, room, and the building form. Keywords:  boarding school, Pendhalungan, reinvigorating tradition  AbstrakPondok pesantren Zainul Hasan Genggong merupakan pendidikan islam yang juga mengajarkan pendidikan umum. Pondok pesantren ini sudah berdiri sejak beberapa tahun yang lalu dengan masih banyak kekurangan desain. Jumlah kamar juga masih perlu ditambah. Karena itulah diperlukan perancangan kembali bangunan ini. perancangan kembali memiliki tujuan untuk meningkatkan dan mengembangkan kualitas pendidikan. Tema rancangan  yang  digunakan  untuk  desain  yang  baru  ini  adalah  reinvigorating  tradition dari  budaya Pendhalungan. Di dalam budaya Pendhalungan terdapat nilai-nilai islam, antara lain konsep Ma’iyyah (kebersamaan), konsep kesederhanaan, dan konsep tidak berlebih-lebihan. Ketiga konsep islam tersebut bersama dengan suasana Pendhalungan ditunjukkan ke dalam seluruh aspek perancangan baru, termasuk ke dalam desain tapak, ruang, dan bentuk bangunan. Kata kunci:  pondok pesantren, Pendhalungan, reinvigorating tradition